Crude glycerin combined with food additives in feeding beef cattle - Costa Almeida, Marco Tulio [UNESP]; Bertocco Ezequiel, Jane Maria [UNESP]; Paschoaloto, Josimari Regina [UNESP]; Carvalho, Vanessa Barbosa de [UNESP]; Perez, Henrique Leal [UNESP]; Favaro, Vanessa Ruiz [UNESP]; D'Aurea, Andre Pastori [UNESP]; Homem Junior, Antonio Carlos [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
The objective of this study was to evaluate the effects of adding crude glycerin with food additives (sodium monensin or essential oils) to the diets of beef cattle on feed intake, ruminal parameters, in vitro digestibility, and production of greenhouse gases. Five ruminally cannulated Nellore steers were randomly assigned in a 5x5 Latin square design. The treatments were: control, without crude glycerin and additives; with essential oils and without crude glycerin; with sodium monensin and without crude glycerin; with essential oils and crude glycerin; and with sodium monensin and crude glycerin. The addition of crude glycerin caused a reduction in dry matter (DM) intake, increase in vitro dry matter digestibility, and decrease in vitro crude protein digestibility, regardless of the food additive. All treatments were effective in maintaining the rumen environment with pH values above 6.2 and ammonia nitrogen concentrations above 10 mg dL(-1). No difference was observed in the production and quality of protozoal and bacterial fractions. The addition of crude glycerin at 200 g kg(-1) DM in the total diet can partially replace corn grain and soybean hulls and be combined with either sodium monensin or essential oil without impairing the rumen fermentation, being effective in reducing gas methane production and, when combined with sodium monensin, enables more efficient utilization of the diet by the animal. Therefore, feedlot experiments at large scales of production should be evaluated to prove these positive results.
Keywords: byproduct; essential oil; ruminal parameters; sodium monensin